Influence of seed ripeness, sarcotesta, drying and storage on germinability of papaya (Carica papaya L.) seed - U. R., Sangakkara (Universiti Putra Malaysia Press, 1995)
Papaya (Carica papaya L.) is a popular tropical fruit which is propagated by seed. However, germination and the procurement of good seedlings are difficult in this species due to the nature of the seed. Thus a series of studies to evaluate the influence of fruit maturity, sarcotesta and drying on germination and production of healthy seedlings was carried out. The characteristics of papaya seed change with fruit maturity. Speed of germination increases with fruit maturity. Thus, the best seed for germination and for the the procurement of healthy seedlings is obtained from ripe or over-ripe fruits. The presence of the sarcotesta reduces germination and increases the number of abnormal seedlings. Incorporation of the sarcotesta in the germination medium of papaya or rice seeds did not inhibit their germination. This suggests that inhibition is caused by the intact sarcotesta rather than inhibitors derived from it. Drying papaya seeds under shade and ambient temperature maintained germinability to a greater degree than when seeds were desiccated in ovens. The reduction of seed moisture below 10% reduced germination significantly, indicating an intermediate behaviour pattern for papaya seeds in contrast to orthodox or recalcitrant seeds.